Race and the politics of solidarity - Hooker, Juliet (Oxford : Oxford University Press, 2009)
In multiracial and multicultural societies, the author argues, the practice of political solidarity has been indelibly shaped by the social fact of race. The starting point should thus be the existence of racialized solidarity itself - how can we create political solidarity when racial and cultural diversity are more or less permanent?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Solidarity -- Political aspects; Race relations; Multiculturalism; Minorities -- Civil rights